Intra-and inter-provenance variability of Ostrya carpinifolia Scop. seedlings - Ivetić Vladan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2015)
Hop Hornbeam (Ostrya carpinifolia Scop.) seedlings from 45 half-sib lines, from three provenances were analyzed. Intra-population variability between half-sib lines was found for morphological attributes of two-year seedlings. In this sense, maternal (seed) trees with the greatest potential for the production of reproductive material may be selected. Interpopulation variability between provenances was found for morphological and physiological attributes, except for the height and dry mass of the two-year seedlings. The influence of half-sib lines and provenances on the concentration of the studied nutrients should be further examined in a larger number of samples. Despite its large potential, Hop Hornbeam is not used for afforestation in Serbia. In those terms, we should work to change attitudes in the selection of the common types of reforestation species. [Projekat Ministarstva nauke Republike Srbije, br. TP 31041: Establishment of Wood Plantations Intended for Afforestation of Serbia]